Evaluasi Kurikulum Pendidikan Islam Berbasis Pesantren dalam Meningkatkan Kompetensi Spiritual dan Sosial Santri (Studi Kasus di Asrama 10 Hurun Inn Pondok Pesantren Darul Ulum Jombang) - Ainun Nikmah Rohmatul Ilmi (Indo Publishing, 2026)
This study aims to evaluate the *pesantren*-based Islamic education curriculum regarding its role in enhancing the spiritual and social competencies of *santri* (students) at Dormitory 10 Hurun Inn, Darul Ulum Islamic Boarding School, Jombang. The study is motivated by the need for an evaluation system capable of objectively measuring the curriculum's success, given that character formation has historically relied on habituation and role modeling without the support of standardized evaluation instruments. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using the interactive model developed by Miles, Huberman, and Saldaña. Data validity was ensured through source triangulation, technique triangulation, member checking, and an audit trail. The findings reveal that the Islamic education curriculum at Dormitory 10 Hurun Inn operates as a